PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SDN 006 TRI MULYA JAYA KECAMATAN UKUI - Murjiyem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in social studies for second-grade students at SDN 006 Tri Mulya Jaya. Of the 20 students, only 9 students (45.00%) achieved mastery learning, while the average score was 50. This research aims to improve student learning outcomes through the application of the CTL (Contextual Teaching and Learning) approach in social studies. This study is a classroom action research (CAR) conducted in two cycles. The data used consist of learning outcomes as well as teacher and student activity data. The results showed that the application of the CTL approach improved learning outcomes and increased teacher and student activity. Teacher activity data showed improvement in each cycle. In the first cycle, the first meeting obtained a score of 22 (50.00%) in the “less” category. In the second meeting of the first cycle, teacher activity increased to a score of 27 (61.36%) in the “sufficient” category. In the second cycle, the first meeting increased to a score of 34 (77.27%) in the “good” category, and in the second meeting of the second cycle increased again to a score of 39 (88.64%) in the “very good” category. Student activity also increased in every meeting of each cycle. In the first cycle, the first meeting obtained a score of 21 (47.73%) in the “less” category. In the second meeting of the first cycle, student activity increased to a score of 25 (56.82%) in the “sufficient” category. In the second cycle, the first meeting showed a further increase to a score of 35 (79.55%) in the “good” category, and at the second meeting of the second cycle student activity increased again to a score of 37 (84.09%) in the “very good” category. Learning outcomes in formative tests (UH I and UH II) also increased from the base score. In the first cycle, 14 students (70%) achieved mastery learning while 6 students (30%) did not. In the second cycle, the number of students who achieved mastery increased to 16 students (80%), while 4 students (20%) did not.